The Effect of Education, Income, and Access to Health Services on the Quality of Life of the Elderly in West Java - Jepri Utomo; Arief Yanto Rukmana; Sulistyo Andarmoyo; Dito Anurogo (Westscience Press, 2023)
This research explores the dynamic interplay between education, income, access to health services, and the quality of life among the elderly in West Java. Utilizing a sample of 120 individuals, the study employs Structural Equation Modeling (SEM-PLS) to analyze the relationships between these key variables. The results reveal that education emerges as a robust predictor, exerting the strongest positive influence on the quality of life among the elderly. Income and access to health services also significantly contribute to well-being, highlighting the multifaceted nature of factors shaping the aging population's quality of life. The findings provide valuable insights for policymakers, practitioners, and researchers aiming to enhance the overall well-being of the elderly in the region.